Predictive value of remnant cholesterol level for all-cause mortality in heart failure patients - Zhao, Lang; Zhao, Xuemei; Tian, Pengchao; Liang, Lin; Huang, Boping; Huang, Liyan; Feng, Jiayu; Zhang, Yuhui; Zhang, Jian (Frontiers in Cardiovascular Medicine, 2023)
Background: Lower cholesterol levels are associated with increased mortality in heart failure (HF) patients. Remnant cholesterol corresponds to all cholesterol not found in high-density lipoprotein (HDL) and low-density lipoprotein (LDL). The prognostic role of remnant cholesterol in HF remains unknown. Objective: To reveal the relationship between the baseline remnant cholesterol level and all-cause mortality in HF patients. Methods: This study enrolled 2823 patients hospitalized for HF. Kaplan–Meier analysis, Cox regression, C-statistic, net reclassification improvement (NRI), and integrated discrimination improvement (IDI) were used to evaluate the prognostic value of remnant cholesterol for all-cause mortality in HF. Results: The mortality rate was lowest in the fourth quartile of remnant cholesterol, which had an adjusted HR hazard ratio (HR) for death of 0.56 [HR: 0.39, 95% confidence interval (CI): 0.46-0.68, P< 0.001] relative to the first quartile. After adjustment, a one-unit increase in the level of remnant cholesterol was associated with a 41% decrease in the risk of all-cause mortality (HR: 0.59, 95% CI: 0.47-0.73, P<0.001). A refinement in risk prediction was observed after adding remnant cholesterol quartile to the original model (ΔC-statistic=0.010, 95% CI: 0.003-0.017; NRI= 0.036, 95% CI: 0.003-0.070; IDI= 0.025, 95% CI: 0.018-0.033; all P< 0.05). Conclusion: Low remnant cholesterol levels are associated with increased all-cause mortality in HF patients. The addition of the remnant cholesterol quartile improved the predictive value over traditional risk factors.